Evaluating the unsteady Casson nanofluid over a stretching sheet with solar thermal radiation: An optimal case study - Jamshed, Wasim; Uma Devi S, Suriya; Goodarzi, Marjan; Prakash, M.; Sooppy Nisar, Kottakkaran; Zakarya, M.; Abdel-Aty, Abdel-Haleem (Case studies in thermal engineering, 2021)
The present study investigates the unsteady flow of a non-Newtonian Casson nanofluid in terms of its thermal transport as well as entropy. The impact of slip condition and solar thremal transport in terms of convection regarding Casson nanofluid flow has been investigated thoroughly. To study the flow behaviors and its thermal transport, the nanofluid is subjected to a slippery surface that is under convective heat. The modeled equations regarding Casson nanofluid flow and heat transfer are abridged by assuming a boundary layer flow along with Roseland approximations. Partial differential equations (PDEs) are used to formulate the governing equations defining the flow problem. After suitable transformation of the equations into Ordinary Differential Equations (ODEs), their self-similar solution is obtained via a numerical technique, namely Keller box. Two distinct categories of nanofluids considered for analysis are Copper-water (Cu−H2O) and Titanium-water (TiO2−H2O). Numerical outcomes are graphically elaborated concerning various flow parameters, including heat transfer, skin friction, Nusselt number, and entropy. Moreover, an enhancement in the Reynolds number along with the effective Brinkman numbers increased the overall entropy in the system. The thermal conductivity amplifies in the case of Casson phenomena rather than conventional fluid. From our findings, it is quite evident that (Cu−H2O) nanofluid is more reliable in terms of heat transfer in comparison with (TiO2−H2O) nanoliquid.